Розвиток швидкісно-силових здібностей учнів під час спортивної ігрової діяльності - Гаврилюк, Валерій Олексійович; Головащенко, Роман Володимирович; Шевц, Вікторія Олександрівна (Український державний університет імені Михайла Драгоманова, 2023)
У статті висвітлюється вплив методу динамічних зусиль на розвиток швидкісно-силових здібностей учнів під час спортивної ігрової діяльності. Досліджувався вплив даного методу на раціональну побудову тренувального процесу, що призводить до зростання функціональних можливостей організму юних футболістів та вдосконалення усього комплексу заходів, відповідальних за підготовку до загальної діяльності. Відповідно до досліджень швидкісно-силові здатності значно зростають у період з 8-9 років до 15-16 років. Спортивно ігрові вправи використовуються в процесі фізкультурно-спортивного тренування та виховання для комплексного вдосконалення рухової діяльності в ускладнених умовах. У найбільшій мірі це дозволяє вдосконалити такі якості і здібності, як спритність, швидкість реакції в поєднанні з швидкістю руху, сили в поєднанні з швидкістю та інших етичних якостей особистості.

The article highlights the influence of the method of dynamic efforts on the development of speed and strength abilities of students during sports and game activities. The impact of this method on the rational construction of the training process, which leads to the growth of the functional capabilities of the body of young football players and the improvement of the entire set of measures responsible for preparation for general activity, was investigated. According to the results of the analysis of the scientific and methodological literature, it can be stated that the method of developing speed and strength abilities of students of general secondary education institutions remains relevant and requires a modernized method of applying physical exercises using the means of sports games in physical culture lessons. According to research, speed-power abilities increase significantly from 8-9 years to 15-16 years. Sports game exercises are used in the process of physical culture and sports training and education for comprehensive improvement of motor activity in difficult conditions. To the greatest extent, it allows you to improve such qualities and abilities as dexterity, speed of reaction in combination with speed of movement, strength in combination with speed and other ethical qualities of the individual.
Keywords: розвиток; швидкісно-силові здібності; спортивні ігри; футбол; тренування; development; speed and strength abilities; sports games; football; training